KEMAMPUAN MEMBACA CEPAT DENGAN METODE SKIMMING SISWA KELAS XI IPS SMA NEGERI 3 MERLUNG TAHUN AJARAN 2016/2017 - Deni Setyo Pamuji (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2017)
The ability to read quickly is important in the learning process. With fast reading students can obtain the needed information from a text reading as much as possible with a minimum of time. This study aimed to describe the ability to read faster class XI IPS SMA N 3 Merlung the academic year 2016/2017. This research uses descriptive quantitative research design. Subjects in this study were students of class XI IPS SMA 3 Merlung totaling 28 people. The data in this study is answer the multiple choice questions, obtained by providing reading tests to students. The conclusion of this study indicate that in general the ability to read fast class XI IPS SMA N 3 Merlung in the school year 2016/2017 is capable of. The ability to read quickly the student with the highest predicate capable of reaching 39%, a predicate is able to reach 46%, and received the title less able to achieve 14%. Thus the average level of the content of reading comprehension class XI IPS SMA N 3 Merlung is 75%, this means that students XI IPS is able to read quickly.